Effect of baseline micronutrient and inflammation status on CD4 recovery post-cART initiation in the multinational PEARLS trial. Issue 3 (June 2019) - Shivakoti, Rupak; Ewald, Erin R.; Gupte, Nikhil; Yang, Wei-Teng; Kanyama, Cecilia; Cardoso, Sandra W.; Santos, Breno; Supparatpinyo, Khuanchai; Badal-Faesen, Sharlaa; Lama, Javier R.; Lalloo, Umesh; Zulu, Fatima; et al.
Summary: Background & aims: Nutritional deficiency and inflammation may impact CD4+ T cell recovery during combination antiretroviral therapy (cART), particularly in resource-limited settings where malnutrition is prevalent. The aim of this study was to investigate the relationship of micronutrient and inflammation biomarkers to CD4 recovery after cART initiation. Methods: We conducted a secondary analysis of a random sub-cohort sample (n = 270) from a multinational randomized trial of cART regimen efficacy among 1571 cART-naïve adults. We measured pre-cART serum levels of micronutrients (Vitamin A, B6, B12, D, total carotenoids, selenium, and iron) and inflammation (C-reactive protein, soluble CD14 (sCD14), IFNγ, TNFα, Interleukin-6, and C-X-C motif chemokine 10 (CXCL10/IP10), EndoCab (IgM)) biomarkers. Biomarker status (i.e. micronutrient deficiency vs. sufficiency and elevated vs. low inflammation) was defined using established cutoffs or quartiles. Mixed-effects linear regression models were used to determine the association of baseline (pre-cART) concentrations of individual biomarkers with CD4 recovery through 96 weeks post-cART initiation. Results: In models adjusting for time-dependent viral load and baseline CD4 count, age, sex, body mass index, country, treatment regimen, anemia and hypoalbuminemia status, pre-cART vitamin D deficiency was associated with lower CD4 recovery (−14.9 cells/mm 3, 95% CI: −27.9, −1.8) compared to sufficiency. In contrast, baseline selenium deficiency (20.8 cells/mm 3, 95% CI: 3.3, 38.3), vitamin A deficiency (35.9 cells/mm 3, 95% CI: 17.6, 54.3) and high sCD14 (23.4 cells/mm 3, 95% CI: 8.9, 37.8) were associated with higher CD4 recovery compared to sufficient/low inflammation status. Conclusions: In summary, baseline vitamin D deficiency was associated with diminished CD4 recovery after cART initiation; impaired CD4 recovery may contribute to the poor clinical outcomes recently observed in individuals with vitamin D deficiency. Vitamin A, selenium and sCD14 were associated with CD4 recovery but future studies are needed to further explore these relationships.